2019
DOI: 10.1111/xen.12549
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of human CD47 reduces phagocytosis of porcine endothelial cells and podocytes by baboon and human macrophages

Abstract: Background Our initial studies utilizing a galactosyl‐α1‐3‐galactosyltransferase gene knockout (GalTKO) pig‐to‐baboon renal transplant model demonstrated that the early development of nephrotic syndrome has been a significant obstacle to the long‐term survival of baboon recipients. We have recently documented that sphingomyelin phosphodiesterase‐3 (SMPDL3b) and CD80 expressed on podocytes in porcine kidney grafts contribute to this complication. We have hypothesized that one regulator of immune function is CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Our recent data indicated that hCD47 expression on porcine endothelial cells or glomerular podocytes inhibited phagocytosis by baboon or human phagocytes 6 . None of the baboons that received mTg GalT‐KO kidneys including hCD47 Tg developed proteinuria, including these two rejectors.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our recent data indicated that hCD47 expression on porcine endothelial cells or glomerular podocytes inhibited phagocytosis by baboon or human phagocytes 6 . None of the baboons that received mTg GalT‐KO kidneys including hCD47 Tg developed proteinuria, including these two rejectors.…”
Section: Discussionmentioning
confidence: 93%
“…Our initial study demonstrated an 83‐day survival of a baboon bearing a life‐supporting GalT‐KO pig kidney graft without rejection, when a vascularized donor pig thymus was co‐transplanted from the same GalT‐KO pig 4 . In fact, survival of up to 193 days has been achieved with a modified immunosuppressive regimen that minimized the development of proteinuria, which is associated with activation of podocytes in kidney grafts during the induction period 5,6 . Recently, after overcoming the early development of proteinuria in baboons, 5,7 we have had multiple baboon recipients bearing GalT‐KO kidney plus vascularized thymic grafts that maintained renal graft function longer than 4 months, even without complement inhibitors (Yamada et al manuscript in preparation).…”
Section: Introductionmentioning
confidence: 99%
“…We have successfully produced hCD47 Tg GalTKO miniature swine that express hCD47 in all blood cell lineages . Endothelial cells isolated from these hCD47 pigs markedly reduced phagocytosis by both human and baboon macrophages …”
Section: Introductionmentioning
confidence: 99%
“…Proteinuria has been described to be triggered by the loss of sphingomyelin phosphodiesterase acid‐like 3b expression on porcine podocytes. Treatments as inoculation of anti‐CD20 antibodies (Rituximab) or transgene expression of human CD47 are reported to prevent proteinuria (Nomura et al., 2019; Shah et al., 2018). Indeed, transgenic pig cells expressing human CD47 avoid phagocytosis by baboon macrophages, preventing xenograft injury and proteinuria (Nomura et al., 2019).…”
Section: Pancreatic Isletsmentioning
confidence: 99%